2016
DOI: 10.1515/nuka-2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of simultaneous time series of indoor, outdoor and soil air radon concentrations, meteorological and seismic data

Abstract: It is well known that the temporal dynamic of indoor and outdoor radon concentrations show complex patterns, which are partly not easy to interpret. Clearly, for physical reasons, they must be related to possibly variable conditions of radon generation, migration and atmospheric dispersion and accumulation. The aim of this study was to analyse long-time series of simultaneously measured indoor and outdoor radon concentrations, together with environmental quantities, which may act as control variables of Rn. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Although there are a few main processes that are responsible for the amount of radon concentration in air, there are many parameters influencing radon behaviour. This was also nicely demonstrated by Fourier analysis of indoor and outdoor time series, which has shown that there is more noise in the time series from outdoor than from indoor radon measurements [ 68 ].…”
Section: Properties Of Radon In Outdoor Environmentmentioning
confidence: 84%
See 3 more Smart Citations
“…Although there are a few main processes that are responsible for the amount of radon concentration in air, there are many parameters influencing radon behaviour. This was also nicely demonstrated by Fourier analysis of indoor and outdoor time series, which has shown that there is more noise in the time series from outdoor than from indoor radon measurements [ 68 ].…”
Section: Properties Of Radon In Outdoor Environmentmentioning
confidence: 84%
“…On the other hand, at noon and during the afternoon there is the largest negative temperature gradient causing the strongest atmosphere mixing, causing the lowest radon concentrations [ 63 , 64 ]. Diurnal variation of the radon concentration has been a subject of many investigations [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] and typical behaviour is presented in Figure 2 (taken from [ 66 ]).…”
Section: Properties Of Radon In Outdoor Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical models have been developed by several researchers in the literature to predict radon behaviour and concentration for various conditions and applications [17,18,[20][21][22]. Several studies in the literature have reported the variation of atmospheric radon and its progenies with changes in meteorological parameters like temperature, pressure, humidity and windspeed [23][24][25]. [26] used these meteorological variables as independent predictors in the development of a multiple linear regression model for estimation and prediction of the time series of radon and thoron progeny concentrations.…”
Section: Introductionmentioning
confidence: 99%